Validity and reliability of the strategic factors and organizational performance scales - Kaliappen, Narentheren (IDOSI Publications, 2013)
The study investigates validity and reliability of small data regarding strategic link of competitive strategy, market orientation and innovation strategy on organizational performance of hotels in Malaysia.Thus, the goodness of measures examined via field experts, academicians and data analysis with SPSS v21.Overall, the alpha coefficients were above 0.8. The result of exploratory factor analysis (EFA) showed all factors loaded more than 0.50.Additionally, the result of normality test showed the data was normal.The findings showed that the instrument was reliable and valid.Therefore, the questionnaire developed was appropriate to be used in investigating the integrated effects of strategic factors on organizational performance of hotels in Malaysia.